Agricultural and rural mechanisation in Nepal: status, issues and options for future - Gauchan, D.; Shrestha, S. (Institute for Inclusive Finance and Development (InM), 2017)
Nepal is a small land-locked mountainous country with diverse agroecologies, culture and agriculture. Agriculture is a key source of economic growth, poverty reduction and environmental sustainability in Nepal. It is the mainstay of the national economy, contributing one third of GDP and providing livelihood to more than two thirds of the population (MoF, 2013). The poverty rate is declining over the last two decades but it is still high with one-quarter of its population (25.1%) living below poverty line (CBS, 2012). Food crops are the major